I saw you in the bathtub, and other folk rhymes - Schwartz, Alvin, 1927-; Hoff, Syd, 1912-2004 (New York : Harper & Row, 1989)
Presents an illustrated collection of traditional folk rhymes, some composed by children.
Keywords: Folk poetry, American; Children's poetry, American; Folk poetry; Children's poetry; American poetry -- Collections; Children's writings